2020
DOI: 10.3389/fmicb.2020.536044
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin 1 Deficiency Leads to Microneme Protein-Mediated Growth Defects in Neospora caninum

Abstract: Neospora caninum is an obligate intracellular protozoan parasite that infects a wide range of mammalian species and causes spontaneous abortion in cattle. N. caninum is exposed to oxidative stress during its life cycle. Oxidoreductase is crucial for parasite response to the environmental stresses. Glutaredoxins (Grxs) are small oxidoreductases of the thioredoxin family proteins that catalyze thiol-disulfide exchange reactions by utilizing electrons from the tripeptide glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 57 publications
(83 reference statements)
0
19
0
3
Order By: Relevance
“…We identified five putative GRXs in N. caninum . Our previous study showed that the GRX1 (NcGRX1) and GRX3 (NcGRX3) of N. caninum are located in the cytoplasm [ 16 ] and NcGRX5 in mitochondria. In the present study, we found that GRX S14 and GRX C5 localize to the apicoplasts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified five putative GRXs in N. caninum . Our previous study showed that the GRX1 (NcGRX1) and GRX3 (NcGRX3) of N. caninum are located in the cytoplasm [ 16 ] and NcGRX5 in mitochondria. In the present study, we found that GRX S14 and GRX C5 localize to the apicoplasts.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that NcGRX1 is important for microneme protein-mediated parasite growth, but that NcGRX3 deficiency does not affect parasite growth [ 16 ]. Our study showed that the deletion of GRX S14 or GRX C5 alone did not affect the growth of N. caninum , which was consistent with previous research on Arabidopsis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations